ChemInform Abstract: Oxidative C—O Cross‐Coupling of 1, 3‐Dicarbonyl Compounds and Their Heteroanalogues with N‐Substituted Hydroxamic Acids and N‐Hydroxyimides. Issue 7 (18th February 2014) - Terent'ev, Alexander O.; Krylov, Igor B.; Timofeev, Vladimir P.; Starikova, Zoya A.; Merkulova, Valentina M.; Ilovaisky, Alexey I.; Nikishin, Gennady I.
Abstract The method applying Co(OAc)2·4H2O/KMnO4 in catalytic amounts [conditions A)] is advantageous compared to the procedure using at least 2 equiv.